A highly specific and sensitive ratiometric fluorescent probe for carbon monoxide and its bioimaging applications. (6th August 2018) - Wang, Zuokai; Geng, Zhuofan; Zhao, Ziyang; Sheng, Wenlong; Liu, Caiyun; Lv, Xiaoyu; He, Qiuxia; Zhu, Baocun
Abstract : A simple highly specific and sensitive ratiometric fluorescent probe has been constructed to monitor carbon monoxide levels in living cells. Abstract : The sensitive and accurate detection of intracellular gasotransmitter carbon monoxide (CO) is of great significance for unraveling its diverse cellular functions. Herein, we report a simple highly specific and sensitive 4-hydroxynaphthalimide-based ratiometric fluorescent probeRatio-CO for monitoring CO levels in living cells. ProbeRatio-CO could quantitatively detect CO in the range of 0–50 μM by the ratiometric fluorescence spectroscopy method and the detection limit was measured to be about 17.9 nM. Additionally, probeRatio-CO has been proven to possess preeminent selectivity towards CO over other bioactive species. Most importantly, the excellent response properties of probeRatio-CO enable its applications in the monitoring of the fluctuations of CO levels in living cells by the ratiometric fluorescence imaging technique, and we thus anticipate that this probe would be a novel tool for further elucidating the biological functions of CO in living systems.